HIV and AIDS: Basic Elements and Priorities - Kartikeyan, S.; Bharmal, R. N.; Tiwari, R. P.; Bisen, P. S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
In June 1981, the Centers for Disease Control and Prevention reported the first evidence of a new disease that would later become known as Acquired Immunodeficiency Syndrome (AIDS). HIV and AIDS: Basic Elements and Priorities is a concise collection of all aspects of this disease, and is a source of readily available knowledge. All currently advocated preventive measures such as health education, condom use, safer sex practices, and treatment of sexually transmitted infections have been incorporated. The key elements of this volume are: - up-to-date information on multiple dimensions of the HIV/AIDS epidemic, - discusses new anti-retroviral therapy / drugs, new drugs under clinical trials and preventive HIV vaccine, - covers current ethical, legal and social issues related to HIV/AIDS, - evaluates general public awareness about HIV/AIDS, - includes a global perspective and information about HIV/AIDS. This volume is an excellent reference for science graduates and post graduates, medical students, research scholars and scientists across the world. This book is recommended by the World Health Organization Eastern Mediterranean Region Office (WHO-EMRO) as a basic resource for medical faculty libraries.
Fundamentals -- Prologue -- Fundamentals of Immunity -- Human Immunodeficiency Virus (HIV) -- Social and Environmental Factors -- Immunopathology -- Natural History of HIV Infection -- Infection Control Methods -- Diagnostic Aspects -- Case Definitions -- Laboratory Diagnosis of HIV Infection -- Laboratory Diagnosis of Common Reproductive Tract and Sexually Transmitted Infections -- Clinical Aspects -- Accidental Occupational Exposure -- HIV-Related Neurological Disorders -- HIV-Related Psychological Disorders -- Co-Infection with HIV and Tuberculosis -- Sexually transmitted infections -- Antiretroviral Therapy -- Traditional ethnomedicinal systems and alternative therapies -- Prevention and Control -- Strategies for Prevention and Control -- Surveillance for HIV -- Counselling -- Voluntary Counselling and Testing Services -- Prevention of Mother-to-Child Transmission -- Human Rights, Legal, and Ethical Issues -- Role of Health Care Providers -- Preventive HIV Vaccine -- Response to the HIV Epidemic in India -- Response to the HIV/AIDS Epidemic in Thailand -- Response to the HIV/AIDS Epidemic in China -- Epilogue.
Keywords: MEDICINE; IMMUNOLOGY; MEDICAL VIROLOGY; EMERGING INFECTIOUS DISEASES; BIOMEDICINE; VIROLOGY; INFECTIOUS DISEASES; IMMUNOLOGY